Development of a web-based interactive infographic module for learning Arabic grammar at a Malaysian university - Abdul Hamid, Mohd Fauzi; Sahrir, Muhammad Sabri; Yahaya, Mohd Firdaus; Muassomah, Muassomah (Intelektual Pustaka Media Utama (IPMU), 2025)
Arabic grammar textbooks often contain complex and detailed explanations that can make them challenging for students to master and understand. The utilization of technology can now help resolve this issue through web-based infographic innovations. Infographics are a method of presenting information that is easy and quick to comprehend, which suits the conveyance of complex information for Arabic grammar learning. Accordingly, this study aims to develop a web-based interactive infographic module for Arabic grammar learning. The design and development research (DDR) approach was adopted to design and develop the module, grounded in the Sidek module construction model, infographics design model (IDM), and constructivism theory. The module’s development process involved a needs analysis phase, a design and development phase, and a usability evaluation phase. The creation of module components and elements involved the consensus of ten experts through the Fuzzy Delphi technique. The content validity of the developed module was assessed by five experts based on a modified version of Russell’s module content validity questionnaire. The study’s findings suggest that the developed module has high content validity. In conclusion, this module has the potential to be utilized by students for self-learning Arabic grammar and is also apt for online learning, offering a more engaging and efficient experience.